FCoV och FIP hos svenska katter – förekomst, hantering i klinikmiljö och information till kattägare - Strand, Linnea (2014)
Feline infectious peritonitis (FIP) is a disease that can affect cats and is caused by a feline coronavirus (FCoV). FCoV is spread via the feacal-oral route and many cats are carriers of the virus. Despite that, very few of the carrier cats develop FIP. The explanation of this phenomenon is that the virus has to mutate to be able to cause FIP and in the majority of the carrier cats this mutation never occurs. FIP is very hard to diagnose because the symptoms are diffuse and a completely accurate diagnosis can almost exclusively be established during a postmortem necropsy. If a cat develops FIP there is currently no cure available and the diseased cat will sooner or later die by itself or is euthanized. The aims of this literature study was to determine how carriers of FCoV or cats with FIP should be handled in animal clinics and hospitals, give examples of what information that may be appropriate to give to owners of these cats and also try to determine how common FCoV and FIP is in Swedish cats.